2019
DOI: 10.23919/saiee.2019.8643146
|View full text |Cite
|
Sign up to set email alerts
|

Rain Attenuation Prediction Using Artificial Neural Network for Dynamic Rain Fade Mitigation

Abstract: Atmospheric processes from which rainfall is formed are complex and cannot be accurately predicted using mathematical or statistical models. In this paper, the backpropagation neural network (BPNN) is trained to predict rainfall rates, and hence attenuation that is likely to be experienced on a link. This study is carried out over the subtropical region of Durban, South Africa (29.8587°S, 31.0218°E). Utilizing the non-linear mapping capability between inputs and outputs, the backpropagation neural network is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Empirical models SAM model [32] Singapore [33] Garcia [34] GSST [66] LU model [68] Karasawa [88] Breakpoint [29] Unified [89] YLO model [12] Statistical models M-K model [90] MARIMA [91] ITU-R P.618 [45] PEARP [92] Das Model 1 [93] Physical models Bryant [37] Crane TC [94] PM Model [95] SC EXCELL [62] Fade models Japan [96] Das model 2 [97] ITU-R P.1623 [98] Dao model [99] Learning-based AANN [100] The SAM model [32] has evolved through some previously published articles [101].…”
Section: Rain Fade Modelsmentioning
confidence: 99%
“…Empirical models SAM model [32] Singapore [33] Garcia [34] GSST [66] LU model [68] Karasawa [88] Breakpoint [29] Unified [89] YLO model [12] Statistical models M-K model [90] MARIMA [91] ITU-R P.618 [45] PEARP [92] Das Model 1 [93] Physical models Bryant [37] Crane TC [94] PM Model [95] SC EXCELL [62] Fade models Japan [96] Das model 2 [97] ITU-R P.1623 [98] Dao model [99] Learning-based AANN [100] The SAM model [32] has evolved through some previously published articles [101].…”
Section: Rain Fade Modelsmentioning
confidence: 99%
“…[6] Feedforward back-propagation neural network (FFBNN) Feedforward back-propagation neural network [8] Supervised machine learning (SML) SVM and SML-based regression algorithm that uses Gaussian process-compatible kernel functions. [10] Artificial neural network (ANN) and k-nearest neighbor (kNN) kNN and ANN (recurrent neural network) [11] Back-propagation neural network (BPNN) BPNN with a sigmoid input function [12] Feed-forward multilayer perceptron (FFMLP) in addition to supervised learning (SL)…”
Section: Refmentioning
confidence: 99%
“…MN Ahuna et al [11] developed a rainfall forecast model based on a back-propagation neural network (BPNN) with four years of data collected. The model's predicted results matched with two years of real rain rate from 2017 to 2018.…”
Section: Advantagesmentioning
confidence: 99%
“…With the development of machine learning, it is gradually being applied to precipitation observation [23][24][25][26][27]. To the best our knowledge, the earliest application of artificial neural network (ANN) to rainfall estimation can be traced back to 1992 when French et al used current data to forecast rainfall an hour later by back propagation (BP) neural network [23].…”
mentioning
confidence: 99%
“…To the best our knowledge, the earliest application of artificial neural network (ANN) to rainfall estimation can be traced back to 1992 when French et al used current data to forecast rainfall an hour later by back propagation (BP) neural network [23]. Similar rainfall measurement method was tested in many regions by Ahuna et al and showed reliable performances [26]. In addition, Michaelides et al used the ANN to fill up missing rainfall data [24], and Lathifah et al identified different precipitation categories based on classification and regression tree (CART) [27].…”
mentioning
confidence: 99%